Evaluating query energy consumption in document stores - Duarte, Duarte (2018)
Today’s system users demand fast answers when querying their own databases. Their impatience still high when waiting for the results of a query when they take more than one or two seconds to appear on the screen. However, having fast querying answers it is not the only aspect that determines the quality of a database system we are using, but also the energy consumption involved with. The development of database systems increasingly economic in terms of energy consumption has led to great technological advances in this area. Today, many of the entities that manage large data base systems pay particular attention to this issue, not only for environmental reasons but also for economic reasons, obviously. In this paper we address the issue of queries energy consumption evaluation in database systems, with particular emphasis to those that are executed in a environment of a document store. Based on the information provided by the execution of a query in MongoDB, we designed and developed a process that determines the energy consumption of queries launched in a document store, approaching different alternatives in query designing, implementation and execution.